Large Dzyaloshinskii-Moriya interaction and room-temperature nanoscale skyrmions in CoFeB/MgO heterostructures - Chen, Runze; Wang, Xinran; Cheng, Houyi; Lee, Kyu-Joon; Xiong, Danrong; Kim, Jun-Young; Li, Sai; Yang, Hongxin; Zhang, Hongchao; Cao, Kaihua; Klaui, Mathias; Peng, Shouzhong; et al. (Cell Reports Physical Science, 2021)
Magnetic skyrmions in heavy metal (HM)/CoFeB/MgO structures are of particular interest for skyrmion-based magnetic tunnel junction (MTJ) devices because of their reliable generation, stability, and readout through purely electrical methods. To optimize the properties, such as stability, a strong Dzyaloshinskii-Moriya interaction (DMI) is required at room temperature. Here, using first-principles calculations, we demonstrate that huge DMI can be obtained in Ir/CoFe structures with an Fe-terminated configuration. Moreover, Brillouin light-scattering measurements show that indeed Ta/Ir/Co20Fe60B20/MgO thin films with perpendicular magnetic anisotropy exhibit a large DMI value (1.13 mJ/m2) when the thickness of the CoFeB layer is 1.1 nm, which can be attributed to the smooth and Fe-rich interface between Ir and CoFeB layers. Furthermore, we observe stable sub-100 nm magnetic skyrmions at room temperature in the Ir/CoFeB/MgO systems by magnetic force microscope. This work paves the way for promoting the application of skyrmions in CoFeB/MgO-based perpendicular anisotropy MTJ structures.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Dzyaloshinskii-Moriya interaction; first-principles calculation; interfacial configuration; room-temperature magnetic skyrmions